Population history and mitochondrial genetic substructure of the rama Amerindians from Nicaragua - Baldi Salas, Norberto Francisco (2016)
The Rama are a coastal population from Southern Nicaragua who in large part were able to resist, at least for a time, the cultural changes and social reorganization brought on by colonial and modern influences. Historical information leaves the Rama origins and biological relationships to nearby extinct and extant groups ambiguous. The objective of this study is to examine the internal genetic microdifferentiation based on the first hipervariable region of the mtDNA from a sample of approximately 20% of the population, and to expand the few available historical and anthropological data on the Rama by exploring the effects of cultural practices and historical events on genetic structure, providing an integrative perspective on the Rama genetic history. When considering differences in the spatial distribution and genetic diversity of the mtDNA haplotypes together with historical information on the Rama, a noteworthy pattern emerges: first, haplotypes are differentially distributed among a central Rama community (Punta Águila) from the other five peripheral communities (AMOVA: Fct = 0.10, p < 0.001) and their distribution is consistent with the historical relocation of this population after their split from Punta Gorda in the 18th century; second, differential genetic signatures found among central and peripheral Rama communities resemble two population histories: one of stability (haplogroup A2) and other of expansion (haplogroup B2), supporting the possibility that these patterns of genetic microdifferentiation between central and peripheral populations resulted from the 18th century unification in southern Nicaragua of the Rama and a group of Voto migrants from Costa Rica that later split and hived off to the Bay of Bluefields.